2011
DOI: 10.1186/1475-2875-10-94
|View full text |Cite
|
Sign up to set email alerts
|

Low referral completion of rapid diagnostic test-negative patients in community-based treatment of malaria in Sierra Leone

Abstract: BackgroundMalaria is hyper-endemic and a major public health problem in Sierra Leone. To provide malaria treatment closer to the community, Médecins Sans Frontières (MSF) launched a community-based project where Community Malaria Volunteers (CMVs) tested and treated febrile children and pregnant women for malaria using rapid diagnostic tests (RDTs). RDT-negative patients and severely ill patients were referred to health facilities. This study sought to determine the referral rate and compliance of patients ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 20 publications
(23 reference statements)
1
43
0
Order By: Relevance
“…Among the studies that reported problems with supervision, most related to health system weaknesses, such as staff shortages and competing priorities,28,35,41,43 insufficient skills,24,39 or a lack of fuel for transportation 24,28. Two reports provided illustrations of how poor supervision can reduce community and CHW confidence, which could potentially undermine the malaria CCM intervention: negative experiences of CHWs with formal health workers in Nigeria led them to bypass health facilities in favor of supervision by community leaders and provision of drug supplies directly from the district stores51; and early evaluation of the HMM program in Uganda found that CHWs and communities were concerned about lack of supervisory support from health workers, which affected motivation 48…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the studies that reported problems with supervision, most related to health system weaknesses, such as staff shortages and competing priorities,28,35,41,43 insufficient skills,24,39 or a lack of fuel for transportation 24,28. Two reports provided illustrations of how poor supervision can reduce community and CHW confidence, which could potentially undermine the malaria CCM intervention: negative experiences of CHWs with formal health workers in Nigeria led them to bypass health facilities in favor of supervision by community leaders and provision of drug supplies directly from the district stores51; and early evaluation of the HMM program in Uganda found that CHWs and communities were concerned about lack of supervisory support from health workers, which affected motivation 48…”
Section: Resultsmentioning
confidence: 99%
“…For the eight studies that reported the proportion of all patients referred, the median referral rate was 17.0% (IQR = 8.0–18.8%)15,18,34,38,41,43,45; the most common reasons for referral (where reported) were signs of severe disease or symptoms that the CHW did not have the capacity to treat. It is not clear whether all cases that should have been referred were referred.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Caregivers may prefer to observe the progression of their child’s fever at home and may not comply with CHW referral advice to visit a health centre. Poor compliance to referral by caregivers has been reported in studies in Uganda and Sierra Leone [33, 34]. There is considerable heterogeneity in national and iCCM guidelines on the referral criteria used in the countries that are currently scaling-up iCCM [35].…”
Section: Discussionmentioning
confidence: 99%
“…To obtain the most accurate data regarding etiologies of febrile illness in rural Sierra Leone, a future study should be conducted that includes outpatient clinics, because a substantial burden of illness does not present to a major referral medical center. 15,16 It will also be important to include children in these future studies, because febrile illness is a significant cause of morbidity and mortality in this population. 17 In conclusion, we found that most febrile patients at a healthcare facility in rural Sierra Leone remained undiagnosed or possibly misdiagnosed as malaria.…”
Section: Discussionmentioning
confidence: 99%